Methods of using exercises form tennis with different movement activities for primary school on the physical training lessons - Shuba L.V (Kharkov National Pedagogical University, 2011)
The problems of physical education of primary school children at the present stage in Ukraine. The question of development of new approaches, related to the differentiated programming of development of motive capabilities of students of first class in the process of the fixed from which will be instrumental in the improvement of decision tasks of physical education at school. We mark the back strength of children from experimental group (boys and girls). Scientific evidence of the elaborated innovative technology of using tennis in physical training lessons.